Relationality: How Moving from Transactional to Transformational Relat ionships Can Reshape Our Lonely World - Jay, David (North Atlantic Books, 2024)
How moving from transactional to transformational relationships and or ganizations can save our democracy, nurture our connections, and make us happier and healthier. Powerful institutions, from schools to tech and social media companies, create breeding grounds for isolation by f ailing to invest in relational work. This obstacle stands in the way o f our fight for racial equity, economic justice, and climate resilienc e. In Relationality, leading asexuality and relationship activist Davi d Jay brings clarity to the crisis with a fresh perspective that expan ds upon the fundamental idea that all entities in the universe are con nected. Jay draws from a range of vivid personal experiences, includin g his time spent helping tech workers and policymakers reform social m edia. This book is for people who believe in the power of relationship s and want to see increased investment in relational work. Its scienti fically grounded framework will help readers foster conversations abou t relational work, establish conditions for relationships to thrive, a nd quantify the impact of them. Equipping professionals and activists involved in nonprofit, political, and other types of relational work w ith the knowledge they need to fight for and utilize resources, Relati onality shares valuable insight on: - The history of why institutions fail to invest in relationships - Reimagining ROI calculations to acco unt for relational work - Using tools of prediction and emergence theo ry to build communities - How stories and data about relationships can help us direct resources toward relational work - Relational economic s and the redistribution of wealth With isolation and loneliness on th e rise in a post-lockdown world, Relationality offers a roadmap to nou rish our connections toward a better, more liberated world—personally, organizationally, and in community.